Detecting the effects of a standardized meal challenge on small bowel motility with MRI in prepared and unprepared bowel. Issue 2 (8th November 2018) - de Jonge, Catharina S.; Menys, Alex; van Rijn, Kyra L.; Bredenoord, Arjan J.; Nederveen, Aart J.; Stoker, Jaap
Abstract: Objective: MRI is increasingly used to evaluate small bowel contractility. The objective of this study was to validate a clinically practical stimulation test (300‐kcal meal) for small bowel motility. Methods: Thirty‐one healthy subjects underwent dynamic MRI to capture global small bowel motility after ±10h fasting, of which 15 underwent bowel preparation consisting of 1 L 2.5% mannitol solution and 16 did not. Each subject underwent (1) a baseline motility scan (2) a food challenge (3) a post‐challenge scan, and (4) second post‐challenge scan (after ±20 minutes). This protocol was repeated within 2 weeks. Motility was quantified using a validated motility assessment technique. Key Results: Motility in prepared subjects at baseline was significantly higher than motility in unprepared subjects (0.36 AU vs 0.18 AU, P  < 0.001). In the prepared group, the food challenge produced an 8% increase in motility ( P  = 0.33) while in the unprepared subjects a significant increase of 30% was observed ( P  < 0.001). Responses to food remained insignificant ( P  = 0.21) and significant ( P  = 0.003), for the prepared and unprepared subjects, respectively, ±20 minutes post food challenge. These results were confirmed in the repeated scan session. Conclusion & Inferences: A significant response to a 300‐kcal meal was measured within 10 minutes in unprepared bowel, supporting the clinical use of this challenge to provoke and assess motility changes. A caloric challenge did not produce an observable increase in motility in mannitol prepared subjects. Abstract : In this article, we present a practical MRI stimulation test and validate it in both mannitol prepared and unprepared healthy subjects to evaluate the stimulation test and provide guidance on MRI preparation for future MRI motility studies.